Penyusunan Indeks Kesejahteraan ibu di Indonesia - Candrawati, Ria; Sitorus, Jeffry Raja Hamonangan (Politeknik Statistika STIS, 2023)
Maternal well-being is important because it affects the quality of life of children. In reality, the level of maternal well-being in Indonesia is still relatively low. This is evidenced by the Maternal Mortality Rate in 2020 of 189 deaths per 100,000 live birth which is still far from the SDGs target. In addition, the level of maternal well-being in Indonesia was ranked 112 out of 179 countries in the world in 2015. A measure is needed that can show the level of maternal well-being in each province to facilitate monitoring of government performance related to improving maternal well-being. Therefore, this study aims to develop a Maternal Wellbeing Index (MWI) in Indonesia in 2021. The stages of compiling the Index refer to the guidelines for the formation of composite indices by the OECD using factor analysis. The results showed that the Maternal Wellbeing Index is composed of three dimensions, namely reproductive status, health service use, and socioeconomic status. The province with the highest MWI is DI Yogyakarta, while the lowest IKI is in Papua Province.